PROFIL KEMAMPUAN KOGNITIF SISWA KELAS VIII SMPN 1 SUNGAI APIT PADA MATERI STRUKTUR TUBUH TUMBUHAN - Fitriani, Raisa; Natalina L, Mariani; Nursal, Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research has been done to describe the cognitive ability of students of grade VIII SMPN 1 Sungai Apit in August until December 2017. This research consists of 2 stages. The first stage is about a written test given to each student class VIII.1 SMP Babussalam for validity and reliability test. The second stage of written test is given to each grade VIII student of SMPN 1 Sungai Apit with the material of plant body structure to be analyzed. The result of this study is the cognitive ability of the students of class VIII of cognitive ability of knowledge (C1) 86.58% good category, cognitive ability of understanding (C2) 86.37% good category, cognitive ability of application (C3) 80.24% category good enough, cognitive ability analysis (C4) 74.87 % less good category, cognitive synthesis ability (C5) 70.04% unfavorable category and cognitive ability evaluation (C6) 60.10% unfavorable category. Based on the analysis of the students of grade VIII SMPN 1 Sungai Apit the cognitive ability level of C1 and C2 both C3 and C3 are good, C4, C5 and C6 are not good.Keywords: Cognitive Ability, Structure Plant Body Material